OBTAINING AND MODELING NANO-SCALE STRUCTURES IN SEMICONDUCTORS - Eshboltayev Iqbol Mamirjonovich; G‘ofurov Saidkamol Zokirjon ogli; Eshboltayev Ikromjon Iqbol ogli (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper presents a scientific analysis of methods for obtaining nano-scale structures in semiconductors, as well as issues related to modeling their physical properties. The influence of nano-scale effects, quantum confinement phenomena, and surface effects on the properties of semiconductor materials is examined. In addition, prospects for designing nano-scale structures based on modern experimental and theoretical approaches are highlighted.